Titanium-based surface conductive corrosion-resistant titanium suboxide ceramic coating, preparation method and application thereof
Patent Information
- Application Number
- CN202611324401.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-27
AI Technical Summary
此类工艺能耗高、设备投入大,且高温处理易导致钛基体发生热变形、晶粒长大,降低基体力学性能;同时高温下亚氧化钛易向金红石相TiO2转化,造成涂层导电性能衰减,难以满足低成本、高性能的规模化制备需求
采用空气气氛下180~220℃低温烧结固化,无需惰性或还原性气氛保护,无需专用高温烧结设备,大幅降低了工艺能耗与生产投入;同时避免了高温处理导致的钛基体热变形、晶粒长大等力学性能劣化问题,也杜绝了高温下亚氧化钛向绝缘金红石相转化的风险,稳定保留了涂层的导电功能,解决了现有高温固结工艺能耗高、基体损伤大、功能相易失效的行业痛点。
Smart Images

Figure CN122978754A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic coating preparation technology on metal surfaces, and particularly to a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate, its preparation method, and its application. Background Technology
[0002] Titanium and titanium alloys are widely used in key components in chemical, environmental protection, and metallurgical industries due to their excellent corrosion resistance, low density, and high specific strength. However, under strong corrosion and electrical conditions, a passivation oxide film is easily formed on the surface of pure titanium substrate, which leads to a decrease in conductivity and a shortened service life. Therefore, it is necessary to prepare functional ceramic coatings through surface coating modification to simultaneously enhance conductivity and improve corrosion protection.
[0003] Titanium suboxides (such as Ti4O7 and Ti3O5) possess both metallic conductivity and excellent chemical stability, making them ideal functional phases for titanium-based surface functional coatings. Currently, the preparation technologies for titanium-based titanium suboxide coatings are mainly divided into two categories: high-temperature consolidation and low-temperature bonding. High-temperature consolidation processes, such as high-temperature solid-state sintering, plasma spraying, and thermal spraying, require operation at temperatures above 800℃. Some processes also require inert or reducing atmosphere protection to prevent high-temperature oxidation of titanium suboxide. These processes are energy-intensive and require significant equipment investment. Furthermore, high-temperature treatment can easily lead to thermal deformation and grain growth in the titanium substrate, reducing its mechanical properties. Simultaneously, at high temperatures, titanium suboxide readily transforms into the rutile phase TiO2, causing a decrease in the coating's conductivity, making it difficult to meet the demands for low-cost, high-performance, large-scale preparation.
[0004] The low-temperature bonding route uses binders to solidify titanium suboxide powder onto the substrate surface. While this method is simple and requires low preparation temperatures, existing solutions have significant drawbacks: When using organic binders, they are prone to degradation and failure under strong acid or charged conditions, leading to a sharp drop in coating adhesion and the potential introduction of insulating phases. When using conventional inorganic binders (such as silicates and silica sols), the compatibility between the binder phase and titanium suboxide is poor, resulting in insufficient coating density and interfacial bonding strength, making the coating susceptible to peeling and corrosion resistance failure in acidic environments. Furthermore, in existing low-temperature coating processes, the poor dispersion stability of water-based slurries easily leads to uneven coating composition. In multi-layer coatings, the distinct interlayer interfaces can easily become channels for corrosive media penetration, further shortening the coating's service life.
[0005] In summary, there is currently a lack of a method in this field for preparing a titanium suboxide ceramic coating on a titanium substrate that can be prepared at low temperatures in an air atmosphere, has high interfacial bonding strength, excellent acid corrosion resistance, and is simple to process, which restricts the industrial promotion and application of this type of functional coating. Summary of the Invention
[0006] The main objective of this invention is to provide a conductive and corrosion-resistant titanium suboxide ceramic coating for titanium substrates, its preparation method, and its application. A stable aqueous titanium suboxide suspension slurry is prepared using aluminum dihydrogen phosphate as an inorganic binder. After being coated and dried layer by layer, it is sintered at a low temperature of 180~220℃ in air. The aluminum polyphosphate binder phase formed by the dehydration condensation of aluminum dihydrogen phosphate achieves a strong bond between the titanium suboxide particles and the titanium substrate. This invention can prepare a functional ceramic coating for titanium substrates with high bonding strength, excellent acid corrosion resistance, and excellent conductivity under low-temperature conditions without inert atmosphere protection.
[0007] The titanium substrate is subjected to degreasing, sandblasting, and acid etching in sequence to obtain a rough and clean surface to be coated. Titanium suboxide powder, aluminum dihydrogen phosphate inorganic binder, sodium polyacrylate dispersant, and deionized water are mixed and thoroughly stirred to obtain a uniform and stable aqueous suspension slurry. The titanium suboxide is Ti4O7 and / or Ti3O5, and the particle size of the titanium suboxide powder is 50nm~500nm. The mass ratio of binder to titanium suboxide powder is 1:2~1:5, the amount of dispersant is 0.5%~2% of the mass of titanium suboxide powder, and the amount of water is 2~5 times the total mass of titanium suboxide powder and aluminum dihydrogen phosphate. The aqueous suspension slurry is uniformly coated onto the surface of a titanium substrate to form a single-layer wet film, which is then dried in an environment of 50~70℃ to remove free water. After the coating cools to room temperature, the coating-drying operation is repeated 3~5 times to obtain a coating precursor with a total dry film thickness of 20~100μm. A titanium substrate with a coating precursor is placed in an air atmosphere and heated to 180-220°C at a rate of 1-3°C / min and held for 0.5-3 hours. Aluminum dihydrogen phosphate forms a continuous phosphate binder phase through a dehydration condensation reaction, and finally a sub-titanium oxide functional ceramic coating is obtained.
[0008] Furthermore, the step of mixing titanium suboxide powder, aluminum dihydrogen phosphate inorganic binder, sodium polyacrylate dispersant, and deionized water, and thoroughly stirring and dispersing them to obtain a uniform and stable aqueous suspension slurry includes: Take an aqueous solution of aluminum dihydrogen phosphate with a mass concentration of 30%~50%, mix it with deionized water and stir evenly to obtain the binder base liquid; Add sodium polyacrylate dispersant to the adhesive base liquid and stir until completely dissolved; the sodium polyacrylate is an anionic polyelectrolyte dispersant. Add titanium suboxide powder to the binder base liquid containing the dispersant, and stir initially to form a premixed slurry; the titanium suboxide powder is Ti4O7 and / or Ti3O5; The premixed slurry was subjected to mechanical stirring and ultrasonic dispersion treatment in sequence to obtain a stable aqueous suspension slurry with a solid content of 25%~35%.
[0009] Furthermore, the sub-titanium oxide powder is composed of Ti4O7 and Ti3O5 in a mass ratio of 1:2 to 2:1.
[0010] Furthermore, the step of forming a continuous phosphate binder phase by the aluminum dihydrogen phosphate through a dehydration condensation reaction includes: During the heat preservation process, the aluminum dihydrogen phosphate gradually loses its water of crystallization; The titanium suboxide particles are encapsulated and bonded to the surface of the titanium matrix by a continuous network structure formed by intermolecular dehydration condensation, and then solidified into a phosphate glass phase bonding layer after cooling.
[0011] Furthermore, the phosphate glass phase bonding layer is an amorphous aluminum polyphosphate continuous network; The continuous network of aluminum polyphosphate simultaneously forms Ti-OP chemical bonds with the oxide layer on the surface of the titanium matrix, and forms physical encapsulation and chemical bonds with the sub-titanium oxide particles.
[0012] Furthermore, the step of uniformly coating the aqueous suspension slurry onto the surface of the titanium substrate to form a single-layer wet film, drying it in an environment of 50~70℃ to remove free moisture, and repeating the coating-drying operation 3~5 times after the coating cools to room temperature includes: The aqueous suspension slurry is coated onto the surface of the titanium substrate by brushing, dip-coating, or spraying, with the thickness of the wet film controlled at 0.2~0.5 mm per coat. After each coating, the titanium substrate is placed in a 60°C oven to dry for 30-60 minutes to evaporate the free moisture in the coating and form a dry film. After each drying process, the titanium substrate is removed from the oven and allowed to cool naturally to room temperature before the next coating is applied. Repeat the above operation 3 to 5 times to finally obtain a coating precursor with a total dry film thickness of 20 to 100 μm.
[0013] Furthermore, the step of removing the titanium substrate from the oven after each drying process, allowing it to cool naturally to room temperature, and then performing the next coating includes: A single drying process removes free water from the slurry, while aluminum dihydrogen phosphate in the dry film retains some water of crystallization and maintains its binding activity. No grinding or roughening treatment is required between layers. During the next coating, the upper slurry and the lower dry film surface will mutually dissolve and bond, forming an integral coating without obvious interlayer interfaces.
[0014] The present invention also provides a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate surface. The coating is a composite ceramic layer attached to the surface of a titanium substrate, comprising a sub-titanium oxide functional phase and a phosphate binder phase. The coating is prepared by the above-described method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate surface.
[0015] Furthermore, the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface includes: The sub-titanium oxide functional phase is Ti4O7 and / or Ti3O5; The aluminum polyphosphate binder phase is an amorphous, continuous network structure that encapsulates titanium suboxide particles and fills the interparticle gaps. A Ti-OP chemically bonded transition layer exists at the interface between the coating and the titanium substrate.
[0016] The present invention also provides an application of a conductive and corrosion-resistant sub-titanium oxide ceramic coating on the surface of a titanium substrate, wherein the titanium substrate with the sub-titanium oxide ceramic coating is placed in an acidic electrolyte system with a pH value of 1 to 6 and used as an anode under a current density of 100 to 2000 A / m².
[0017] The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate provided in the above embodiments has the following beneficial effects: The process employs low-temperature sintering and curing at 180~220℃ in an air atmosphere, eliminating the need for inert or reducing atmosphere protection and dedicated high-temperature sintering equipment, thus significantly reducing process energy consumption and production investment. At the same time, it avoids the mechanical property degradation problems such as thermal deformation and grain growth of the titanium matrix caused by high-temperature treatment, and also eliminates the risk of the transformation of sub-titanium oxide into the insulating rutile phase at high temperatures, stably preserving the conductive function of the coating. This solves the industry pain points of high energy consumption, large substrate damage, and easy failure of functional phases in existing high-temperature consolidation processes.
[0018] Using aluminum dihydrogen phosphate as an inorganic binder, a continuous amorphous aluminum polyphosphate bonding network is formed through low-temperature dehydration condensation. This binder phase not only physically encapsulates and firmly binds titanium suboxide particles, but also forms a Ti-OP chemical bonding interface with the oxide layer on the titanium substrate surface, significantly improving the bonding strength between the coating and the substrate. The aluminum polyphosphate inorganic binder phase itself possesses excellent resistance to strong acid corrosion, avoiding the defects of easy degradation and failure of organic binders. It can be stably used for a long time in acidic environments, effectively solving the problems of weak adhesion and poor corrosion resistance of existing low-temperature bonding coatings.
[0019] A stable suspension slurry adapted to the acidic aluminum dihydrogen phosphate system was constructed using an anionic sodium polyacrylate dispersant, ensuring the uniformity of the coating components. Combined with the process design of layer-by-layer coating and control of residual crystal water, interlayer mutual dissolution and bonding can be achieved, eliminating obvious interlayer interface defects, blocking the penetration channels of corrosive media, and significantly improving the overall density and service reliability of the coating. Attached Figure Description
[0020] Figure 1 This is a flowchart of a method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate, as provided in an embodiment of the present invention. Figure 2 This is a low-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the surface of the titanium substrate prepared in Example 1 of this invention. Figure 3 This is a high-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface prepared in Example 1 of this invention; Figure 4 This is a high-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the surface of the titanium substrate prepared in Example 2 of this invention; Figure 5 This is a high-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface prepared in Example 3 of this invention; Figure 6 This is a high-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface prepared in Example 4 of this invention. Figure 7 This is a low-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface prepared in Comparative Example 4 of this invention; Figure 8 This is a high-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface prepared in Comparative Example 4 of this invention; Figure 9 This is a low-magnification SEM image of the conductive and corrosion-resistant sub-titanium oxide ceramic coating on the surface of the titanium substrate prepared in Comparative Example 5 of this invention. Figure 10 This is a comparison table of coating performance parameters between various embodiments and comparative examples of the present invention; The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0022] Reference Figure 1 This is a schematic flowchart of a method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate, as proposed in this invention, including the following steps: S1, the titanium substrate is sequentially degreased, sandblasted, and acid-etched to obtain a rough and clean surface to be coated; S2, mix titanium suboxide powder, aluminum dihydrogen phosphate inorganic binder, sodium polyacrylate dispersant and deionized water, and stir and disperse thoroughly to obtain a uniform and stable aqueous suspension slurry; the titanium suboxide is Ti4O7 and / or Ti3O5, and the particle size of the titanium suboxide powder is 50nm~500nm; the mass ratio of binder to titanium suboxide powder is 1:2~1:5, the amount of dispersant is 0.5%~2% of the mass of titanium suboxide powder, and the amount of water is 2~5 times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate; S3, the aqueous suspension slurry is uniformly coated on the surface of the titanium substrate to form a single-layer wet film, and dried in an environment of 50~70℃ to remove free water; after the coating cools to room temperature, the coating-drying operation is repeated 3~5 times to obtain a coating precursor with a total dry film thickness of 20~100μm. S4. The titanium substrate with the coating precursor is placed in an air atmosphere and heated to 180-220℃ at a rate of 1-3℃ / min and held for 0.5-3h. Aluminum dihydrogen phosphate forms a continuous phosphate binder phase through dehydration condensation reaction, and finally a sub-titanium oxide functional ceramic coating is obtained.
[0023] As described in step S1 above, the surface pretreatment of the titanium substrate is used to remove various surface contaminants and construct a roughened, activated interface, providing a clean and highly adhesive substrate for subsequent coating adhesion. The titanium substrate is ultrasonically cleaned with acetone or anhydrous ethanol to remove surface-adhered grease and organic contaminants. The cleaning time is controlled at 10-20 minutes. After cleaning, the substrate is removed and the solvent is drained. The cleaned titanium substrate is then sandblasted with 20-30 mesh corundum or black corundum abrasive. The sandblasting pressure is maintained at 0.4-0.6 MPa, and the distance between the blasting nozzle and the substrate surface is kept at 100-150 mm, uniformly sweeping across the entire area to be coated. Sandblasting can form a uniform micro-uneven structure on the substrate surface, controlling the surface roughness Ra within the range of 2-5 μm, increasing the mechanical interlocking sites between the coating and the substrate. The sandblasted titanium substrate is then immersed in a boiling oxalic acid solution with a mass concentration of 8%-12% for acid etching treatment for 1-3 hours. The acid etching process, building upon the roughening effect of sandblasting, further etches a fine honeycomb-like micro-pit structure, increasing the specific surface area of the substrate and activating surface titanium atoms to create reaction sites for interfacial chemical bonding. After acid etching, the titanium substrate is removed and ultrasonically cleaned with deionized water to thoroughly remove residual acid and reaction products. After drying, a rough, clean surface with high bonding activity is obtained for coating.
[0024] As described in step S2 above, the aqueous suspension slurry serves as a precursor medium for coating formation, and the component matching and dispersion state directly determine the structural uniformity and performance stability of the final coating. A 30%–50% (w / w) aqueous solution of aluminum dihydrogen phosphate is mixed with a measured amount of deionized water and continuously stirred to form a homogeneous binder base liquid. The total amount of water used is 2–5 times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. An anionic sodium polyacrylate dispersant is added to the binder base liquid and continuously stirred until the dispersant is completely dissolved. The amount of dispersant used is 0.5%–2% of the mass of the titanium suboxide powder. Sodium polyacrylate can provide electrostatic steric hindrance in acidic binder systems, providing suitable conditions for subsequent stable powder dispersion. The titanium suboxide powder is slowly added to the binder base liquid containing the dissolved dispersant, and the material is gradually added during stirring to form a premixed slurry. The titanium suboxide powder is Ti4O7 and / or Ti3O5, with a particle size controlled in the range of 50nm to 500nm. The mass ratio of binder to titanium suboxide powder is controlled in the range of 1:2 to 1:5. The premixed slurry is subjected to mechanical stirring and ultrasonic dispersion treatment in sequence, and the solid content of the final slurry is adjusted to 25% to 35%. After dispersion, the slurry particles are uniformly distributed and can remain stably suspended for a long time under static conditions, without easily agglomerating or settling.
[0025] As described in step S3 above, layer-by-layer coating and gradient drying are used to control the coating forming accuracy, avoid cracking, sagging, and peeling caused by excessive thickness in a single coating, and ensure that the overall coating structure is uniform and dense. The aqueous suspension slurry can be evenly applied to the titanium substrate surface to be coated using brushing, dip-coating, or spraying methods. The wet film thickness of a single coating is controlled between 0.2 and 0.5 mm. The slurry is spread evenly without accumulation or overflow at the edges. After coating, the titanium substrate is transferred to an oven for drying. The drying temperature is set at 60°C, and the holding time is controlled between 30 and 60 minutes. At this temperature, only free water in the slurry is removed, while the binder component retains some water of crystallization. A fully hardened, dense film layer will not form on the surface, thus avoiding a decrease in interlayer adhesion. After drying, the titanium substrate is removed and allowed to cool naturally to room temperature before proceeding to the next coating cycle. The residual water of crystallization on the surface of the lower dry film can mutually dissolve and bond with the newly coated slurry, eliminating the need for surface roughening and achieving tight interlayer bonding, thus removing obvious delamination interfaces. Repeating the coating and drying process 3 to 5 times yields a coating precursor with a total dry film thickness of 20 to 100 μm. The overall structure is continuous and uniform, providing excellent forming conditions for the sintering and curing process.
[0026] As described in step S4 above, the sintering and curing process achieves a strong bond between the coating and the substrate. The formed coating precursor is directly placed in a sintering device with an air atmosphere, eliminating the need for inert or reducing gases for protection throughout the process. This simplifies the process requirements and reduces equipment investment in the preparation stage. A slow heating rate of 1-3°C / min ensures a gentle temperature gradient, preventing the rapid vaporization and escape of residual moisture in the precursor and avoiding structural defects such as blistering and cracking in the coating. This also ensures uniform condensation reaction of the binder phase components. After heating to 180-220°C, the temperature is held for 0.5-3 hours. During this holding period, aluminum dihydrogen phosphate gradually removes residual water of crystallization, undergoing intermolecular dehydration condensation to form a continuous aluminum polyphosphate network structure. The aluminum polyphosphate binder phase tightly encapsulates the titanium suboxide functional particles, filling the gaps between the particles. Simultaneously, it reacts with the oxide layer on the surface of the titanium substrate to form a Ti-OP chemically bonded transition layer, combining mechanical intercalation and chemical bonding to significantly improve the bonding strength between the coating and the substrate. After the heat treatment is completed, the furnace is cooled to room temperature to obtain a complete titanium suboxide functional ceramic coating. The final coating structure is dense and uniform, possessing both excellent electrical conductivity and resistance to strong acid corrosion, enabling it to operate stably for a long time under complex corrosive conditions.
[0027] The present invention will be specifically described below through examples and comparative examples.
[0028] Example 1 TA2 pure titanium sheet with dimensions of 100mm × 50mm × 2mm was selected as the substrate to be treated. The titanium substrate was ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface rolling grease and adhering contaminants. After removal, the surface solvent was drained. The surface of the titanium substrate to be coated was then sandblasted using 24-mesh brown corundum abrasive. The sandblasting pressure was maintained at 0.5MPa, the distance between the spray gun and the substrate surface was kept at 120mm, and the spray gun was moved at a uniform speed to cover the entire area to be treated, resulting in a uniformly rough surface morphology with a roughness Ra controlled at approximately 3μm. The sandblasted titanium substrate was then immersed in a boiling 10% oxalic acid solution for acid etching for 2 hours. After etching, the substrate was removed and ultrasonically cleaned with deionized water for 10 minutes to remove residual acid and etching products. It was then dried in an 80℃ oven to obtain a rough, clean, activated surface to be coated.
[0029] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base solution containing the dissolved dispersant. The addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 min, and then ultrasonically dispersed for 20 min to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0030] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to 0.3 mm, and the slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 minutes to remove free water from the slurry, ensuring that the aluminum dihydrogen phosphate in the dry film retained an appropriate proportion of water of crystallization. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The lower dry film and the upper slurry layer mutually dissolved and bonded at the interface, eliminating the need for additional grinding and roughening treatment. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. The coating was continuous and uniform, without obvious delamination interfaces or cracking defects.
[0031] A titanium substrate with the coating precursor is placed in a muffle furnace under an air atmosphere throughout the process, without the need for inert or reducing protective gases. The temperature is slowly increased to 200°C at a rate of 2°C / min, and held for 2 hours. During this holding period, aluminum dihydrogen phosphate gradually removes its remaining water of crystallization and undergoes intermolecular dehydration condensation, forming a continuous aluminum polyphosphate bonding network that encapsulates the titanium suboxide particles and forms a chemically bonded interface with the titanium substrate surface. After the holding period, the substrate is allowed to cool naturally to room temperature in the furnace. Upon removal, a conductive and corrosion-resistant titanium suboxide ceramic coating is obtained on the surface of the titanium substrate.
[0032] Performance testing showed that the coating had an oxygen evolution potential of 1.58V vs. SCE at a current density of 50mA / cm²; and the enhanced lifetime test verified that the coating had a failure time of 120h.
[0033] Figure 2 The image shows the surface morphology of the coating at low magnification. The overall morphology of the coating is uniform and continuous, consisting of a three-dimensional network structure formed by the stacking and overlapping of titanium suboxide particle aggregates, with interconnected pores of varying sizes distributed between the aggregates. The coating surface shows no obvious through-cracks or large-area peeling defects. The particle aggregates are uniformly distributed, and no localized component segregation is observed, indicating that layer-by-layer coating and low-temperature sintering processes can produce a structurally complete, formed coating.
[0034] Figure 3 The microstructure of the coating under high magnification clearly shows that the surface of the titanium suboxide particles is uniformly coated with a continuous binder phase, and the gaps between the particles are fully filled by the binder phase. Adjacent particles are connected as a whole by bonding. The binder phase exhibits a dense amorphous morphology and is tightly bonded to the titanium suboxide particles without obvious interfacial gaps. This indicates that the aluminum polyphosphate binder phase formed by the dehydration condensation of aluminum dihydrogen phosphate can effectively consolidate the functional particles and provide the coating with good interfacial bonding strength and corrosion resistance barrier.
[0035] Example 2 TA2 pure titanium sheet with dimensions of 100mm × 50mm × 2mm was selected as the substrate to be treated. The titanium substrate was ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface rolling grease and adhering contaminants. After removal, the surface solvent was drained. The surface of the titanium substrate to be coated was then sandblasted using 24-mesh brown corundum abrasive. The sandblasting pressure was maintained at 0.5MPa, the distance between the spray gun and the substrate surface was kept at 120mm, and the spray gun was moved at a uniform speed to cover the entire area to be coated, resulting in a uniformly rough surface with a roughness Ra controlled at approximately 3μm. The sandblasted titanium substrate was then immersed in a boiling 10% oxalic acid solution for acid etching for 2 hours. After etching, the substrate was removed and ultrasonically cleaned with deionized water for 10 minutes to remove residual acid and etching products. It was then dried in an 80℃ oven to obtain a rough, clean, activated surface to be coated.
[0036] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. Pure Ti4O7 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base solution containing the dissolved dispersant. The addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 min, and then ultrasonically dispersed for 20 min to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0037] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to 0.3 mm, and the slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 minutes to remove free water from the slurry, ensuring that the aluminum dihydrogen phosphate in the dry film retained an appropriate proportion of water of crystallization. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The lower dry film and the upper slurry layer mutually dissolved and bonded at the interface, eliminating the need for additional grinding and roughening treatment. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. The coating was continuous and uniform, without obvious delamination interfaces or cracking defects.
[0038] A titanium substrate with the coating precursor is placed in a muffle furnace under an air atmosphere throughout the process, without the need for inert or reducing protective gases. The temperature is slowly increased to 200°C at a rate of 2°C / min, and held for 2 hours. During this holding period, aluminum dihydrogen phosphate gradually removes its remaining water of crystallization and undergoes intermolecular dehydration condensation, forming a continuous aluminum polyphosphate bonding network that encapsulates the titanium suboxide particles and forms a chemically bonded interface with the titanium substrate surface. After the holding period, the substrate is allowed to cool naturally to room temperature in the furnace. Upon removal, a conductive and corrosion-resistant titanium suboxide ceramic coating is obtained on the surface of the titanium substrate.
[0039] Performance testing showed that the coating had an oxygen evolution potential of 1.52V vs. SCE at a current density of 50mA / cm²; and the enhanced lifetime test verified that the coating had a failure time of 135h.
[0040] Figure 4 The image shows a SEM image of the coating prepared in this embodiment. Within the field of view, the coating exhibits a complex and dense microstructure. A continuous aluminum polyphosphate binder phase uniformly coats the surface of the titanium suboxide particles, filling the tiny gaps between the particles and forming a smooth and delicate substrate morphology. In some areas, the uneven structure formed by the aggregation and stacking of titanium suboxide particles is visible, with a small number of uniformly sized micropores distributed between the clusters. Overall, there are no through cracks or particle peeling defects.
[0041] This morphology corresponds to the curing effect of a pure Ti4O7 single-phase system. The highly conductive Ti4O7 phase can construct a more continuous conductive path. Combined with a fully cured phosphate binder phase, it can further improve conductivity and service stability while ensuring the integrity of the coating structure.
[0042] Example 3 TA2 pure titanium sheet with dimensions of 100mm × 50mm × 2mm was selected as the substrate to be treated. The titanium substrate was ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface rolling grease and adhering contaminants. After removal, the surface solvent was drained. The surface of the titanium substrate to be coated was then sandblasted using 24-mesh brown corundum abrasive. The sandblasting pressure was maintained at 0.5MPa, the distance between the spray gun and the substrate surface was kept at 120mm, and the spray gun was moved at a uniform speed to cover the entire area to be coated, resulting in a uniformly rough surface with a roughness Ra controlled at approximately 3μm. The sandblasted titanium substrate was then immersed in a boiling 10% oxalic acid solution for acid etching for 2 hours. After etching, the substrate was removed and ultrasonically cleaned with deionized water for 10 minutes to remove residual acid and etching products. It was then dried in an 80℃ oven to obtain a rough, clean, activated surface to be coated.
[0043] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. The titanium suboxide powder was a mixture of Ti4O7 and Ti3O5 in a 1:1 mass ratio, with a median particle size of 200 nm. The mixed powder was slowly added to the binder base solution containing the dispersant, and the addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, and then ultrasonically dispersed for 20 minutes to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0044] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to 0.3 mm, and the slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 minutes to remove free water from the slurry, ensuring that the aluminum dihydrogen phosphate in the dry film retained an appropriate proportion of water of crystallization. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The lower dry film and the upper slurry layer mutually dissolved and bonded at the interface, eliminating the need for additional grinding and roughening treatment. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. The coating was continuous and uniform, without obvious delamination interfaces or cracking defects.
[0045] A titanium substrate with the coating precursor is placed in a muffle furnace under an air atmosphere throughout the process, without the need for inert or reducing protective gases. The temperature is slowly increased to 200°C at a rate of 2°C / min, and held for 2 hours. During this holding period, aluminum dihydrogen phosphate gradually removes its remaining water of crystallization and undergoes intermolecular dehydration condensation, forming a continuous aluminum polyphosphate bonding network that encapsulates the titanium suboxide particles and forms a chemically bonded interface with the titanium substrate surface. After the holding period, the substrate is allowed to cool naturally to room temperature in the furnace. Upon removal, a conductive and corrosion-resistant titanium suboxide ceramic coating is obtained on the surface of the titanium substrate.
[0046] Performance testing showed that the coating had an oxygen evolution potential of 1.54V vs. SCE at a current density of 50mA / cm²; and the enhanced lifetime test verified that the coating had a failure time of 140h.
[0047] Figure 5 This is an SEM image of the titanium suboxide ceramic coating on the surface of the titanium substrate prepared in this embodiment. The coating density is significantly improved within the field of view. The continuous aluminum polyphosphate binder phase fully covers the titanium suboxide particle clusters, forming a flat and continuous phase structure. The particle outline is completely wrapped by the binder phase, with only a small number of uniform closed micropores remaining locally. There are no through cracks or interface peeling defects.
[0048] This morphology corresponds to the curing effect of a Ti4O7 and Ti3O5 compound system in equal proportions. The two crystal particles are graded to fill the gaps in the stack, and with the uniformly cured phosphate binder phase, the overall density of the coating can be improved while maintaining the continuity of the conductive path, thus further optimizing the corrosion resistance service life.
[0049] Example 4 TA2 pure titanium sheet with dimensions of 100mm × 50mm × 2mm was selected as the substrate to be treated. The titanium substrate was ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface rolling grease and adhering contaminants. After removal, the surface solvent was drained. The surface of the titanium substrate to be coated was then sandblasted using 24-mesh brown corundum abrasive. The sandblasting pressure was maintained at 0.5MPa, the distance between the spray gun and the substrate surface was kept at 120mm, and the spray gun was moved at a uniform speed to cover the entire area to be coated, resulting in a uniformly rough surface with a roughness Ra controlled at approximately 3μm. The sandblasted titanium substrate was then immersed in a boiling 10% oxalic acid solution for acid etching for 2 hours. After etching, the substrate was removed and ultrasonically cleaned with deionized water for 10 minutes to remove residual acid and etching products. It was then dried in an 80℃ oven to obtain a rough, clean, activated surface to be coated.
[0050] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. The titanium suboxide powder was a mixture of Ti4O7 and Ti3O5 in a mass ratio of 1:2, with a median particle size of 200 nm. The mixed powder was slowly added to the binder base solution containing the dispersant, and the addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, and then ultrasonically dispersed for 20 minutes to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0051] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to be 0.3 mm. The slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 minutes to remove free water from the slurry, ensuring that the aluminum dihydrogen phosphate in the dry film retained an appropriate proportion of water of crystallization. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The lower dry film and the upper slurry layer mutually dissolved and bonded at the contact interface, eliminating the need for additional grinding and roughening treatment. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. The coating was continuous and uniform, without obvious delamination interfaces or cracking defects.
[0052] A titanium substrate with the coating precursor is placed in a muffle furnace under an air atmosphere throughout the process, without the need for inert or reducing protective gases. The temperature is slowly increased to 200°C at a rate of 2°C / min, and held for 2 hours. During this holding period, aluminum dihydrogen phosphate gradually removes its remaining water of crystallization and undergoes intermolecular dehydration condensation, forming a continuous aluminum polyphosphate bonding network that encapsulates the composite titanium suboxide particles and forms a chemically bonded interface with the titanium substrate surface. After the holding period, the substrate is allowed to cool naturally to room temperature in the furnace. Upon removal, a conductive and corrosion-resistant titanium suboxide ceramic coating is obtained on the surface of the titanium substrate.
[0053] Performance testing showed that the coating had an oxygen evolution potential of 1.56V vs. SCE at a current density of 50mA / cm²; and the enhanced lifetime test verified that the coating had a failure time of 145h.
[0054] Figure 6This is a SEM image of the titanium suboxide ceramic coating on the titanium substrate surface prepared in this embodiment. Within the field of view, the coating exhibits a composite microstructure of mixed crystalline particles. A continuous aluminum polyphosphate binder phase uniformly coats titanium suboxide particles of different morphologies. The interface between the particles and the binder is tight, with no obvious gaps or peeling. Locally, granular and flaky particles are visible interlocking and stacked. The pores are mostly uniformly sized closed micropores. Overall, there are no through-cracks or large-area peeling defects.
[0055] This morphology corresponds to the curing effect of a 1:2 mixture of Ti4O7 and Ti3O5. The high proportion of Ti3O5 particles can effectively fill the stacking gaps, further improving the overall density of the coating. Combined with the continuous conductive pathways constructed by Ti4O7, the two work synergistically to give the coating both good structural stability and conductivity, thus further improving its service life.
[0056] Example 5 TA2 pure titanium sheet with dimensions of 100mm × 50mm × 2mm was selected as the substrate to be treated. The titanium substrate was ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface rolling grease and adhering contaminants. After removal, the surface solvent was drained. The surface of the titanium substrate to be coated was then sandblasted using 24-mesh brown corundum abrasive. The sandblasting pressure was maintained at 0.5MPa, the distance between the spray gun and the substrate surface was kept at 120mm, and the spray gun was moved at a uniform speed to cover the entire area to be coated, resulting in a uniformly rough surface with a roughness Ra controlled at approximately 3μm. The sandblasted titanium substrate was then immersed in a boiling 10% oxalic acid solution for acid etching for 2 hours. After etching, the substrate was removed and ultrasonically cleaned with deionized water for 10 minutes to remove residual acid and etching products. It was then dried in an 80℃ oven to obtain a rough, clean, activated surface to be coated.
[0057] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the total mass of the titanium suboxide powder. The titanium suboxide powder was a mixture of Ti4O7 and Ti3O5 in a mass ratio of 2:1, with a median particle size of 200 nm. The mixed powder was slowly added to the binder base solution containing the dispersant, and the addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, and then ultrasonically dispersed for 20 minutes to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0058] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to 0.3 mm, and the slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 min to remove free water from the slurry, ensuring that the aluminum dihydrogen phosphate in the dry film retained an appropriate proportion of water of crystallization. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The lower dry film and the upper slurry layer mutually dissolved and bonded at the contact interface, eliminating the need for additional grinding and roughening treatment. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. The coating was continuous and uniform overall, without obvious delamination interfaces or cracking defects.
[0059] A titanium substrate with the coating precursor is placed in a muffle furnace, maintaining an air atmosphere throughout the process without the need for inert or reducing protective gases. The temperature is slowly increased to 200°C at a rate of 2°C / min, and held for 2 hours. During this holding period, aluminum dihydrogen phosphate gradually removes its remaining water of crystallization and undergoes intermolecular dehydration condensation, forming a continuous aluminum polyphosphate bonding network that encapsulates the composite titanium suboxide particles and forms a chemically bonded interface with the titanium substrate surface. After the holding period, the substrate is allowed to cool naturally to room temperature in the furnace. Upon removal, a conductive and corrosion-resistant titanium suboxide ceramic coating is obtained on the titanium substrate surface.
[0060] Performance testing showed that the coating had an oxygen evolution potential of 1.53V vs. SCE at a current density of 50mA / cm². Enhanced lifetime testing verified that the coating had a failure time of 148h, exhibiting the best service stability among all compound systems.
[0061] Comparative Example 1 TA2 pure titanium sheet of the same specifications as in Example 1 was selected as the substrate to be treated. The substrate pretreatment process and parameters were consistent with those in Example 1, and finally a rough and clean activated surface to be coated was obtained.
[0062] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base solution, accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. No sodium polyacrylate dispersant was added during the preparation process. The premixed slurry was first mechanically stirred for 30 minutes, followed by ultrasonic dispersion for 20 minutes to obtain an aqueous suspension slurry. After standing for 30 minutes, the slurry showed obvious stratification and sedimentation, with a clear boundary between the upper clear layer and the lower precipitate, indicating poor suspension stability.
[0063] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The wet film thickness of each coating was controlled to be 0.3 mm, and the slurry was spread evenly without local accumulation. After coating, the titanium substrate was placed in a 60℃ oven for 45 min to remove free moisture from the slurry. After drying, the titanium substrate was removed and allowed to cool naturally to room temperature before proceeding to the next coating operation. The coating and drying process was repeated four times, resulting in a coating precursor with a total dry film thickness of approximately 60 μm. Due to uneven slurry dispersion, the coating exhibited local component agglomeration and thickness fluctuations.
[0064] The titanium substrate with the coating precursor was placed in a muffle furnace and kept in an air atmosphere throughout. The temperature was slowly increased to 200°C at a rate of 2°C / min and held for 2 hours. After the holding period, the substrate was allowed to cool naturally to room temperature in the furnace. The resulting titanium suboxide ceramic coating was obtained without a dispersant.
[0065] The final coating surface showed localized loose areas and uneven thickness. The enhanced life test verified that the coating failure time was 55 hours. The oxygen evolution potential at a current density of 50 mA / cm² was 1.78 V vs. SCE, as determined by the linear sweep voltammetry method. This performance was far lower than the corresponding level in Example 1, verifying the key role of the dispersant in the suspension stability of the slurry and the service performance of the coating.
[0066] Comparative Example 2 TA2 pure titanium sheet of the same specifications as in Example 1 was selected as the substrate to be treated. The substrate pretreatment process and parameters were consistent with those in Example 1, and finally a rough and clean activated surface to be coated was obtained.
[0067] The slurry preparation process and component parameters were consistent with those in Example 1. A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base liquid. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant was added to the binder base liquid and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base liquid containing the dispersant. The addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 min and then ultrasonically dispersed for 20 min to finally obtain a stable aqueous suspension slurry with a solid content of 30%.
[0068] The aqueous suspension slurry was applied to the titanium substrate surface in one go using air spraying. The wet film thickness was about 1.2 mm. The overall thickness of the slurry was relatively large, and there was slight drip accumulation in some areas. After coating, the titanium substrate was placed in a 60℃ oven to dry for 45 min. During the drying process, the resistance to the outward migration of moisture inside the thick film was relatively large. The surface layer formed a film and sealed first, and the escape of internal water vapor was hindered.
[0069] After drying, the titanium substrate was placed directly into a muffle furnace, and the entire process was carried out in an air atmosphere. The temperature was slowly increased to 200°C at a rate of 2°C / min, and the holding time was set to 2 hours. During the heating and holding process, the residual moisture and crystal water in the thick film were concentratedly removed. The volume shrinkage stress could not be released layer by layer, and a large number of through cracks appeared inside the coating. In some areas, the coating peeled off due to stress concentration, and the substrate was partially exposed.
[0070] After the heat preservation process, the coating was naturally cooled to room temperature in the furnace. Upon removal, a titanium suboxide ceramic coating prepared by a single thick coating was obtained. The overall structural integrity of the coating was poor, with significant cracks and peeling defects. The enhanced life test verified that the coating failure time was 25 hours. The oxygen evolution potential at a current density of 50 mA / cm² was measured by linear sweep voltammetry to be 1.95 V vs. SCE, which is much lower than that of the example sample prepared by multiple thin coating processes. This verifies the necessity of multiple thin coating processes to ensure the structural integrity and service performance of the coating.
[0071] Comparative Example 3 This comparative example uses TA2 pure titanium sheet of the same specifications as in Example 1 as the substrate to be treated. The substrate pretreatment process and parameters are consistent with those in Example 1, resulting in a rough and clean activated surface to be coated. The slurry preparation process and component parameters are consistent with those in Example 1. A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate is mixed with deionized water and stirred continuously to form a binder base liquid. The total amount of water used is three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. Anionic sodium polyacrylate dispersant is added to the binder base liquid and stirred continuously until completely dissolved. The amount of dispersant used is 1% of the mass of the titanium suboxide powder. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm is slowly added to the binder base liquid containing the dissolved dispersant. The addition process is accompanied by low-speed stirring to form a premixed slurry. The mass ratio of binder to titanium suboxide powder is controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, and then ultrasonically dispersed for 20 minutes to finally obtain a stable water-based suspension slurry with a solid content of 30%.
[0072] The coating and drying processes were consistent with those in Example 1. The aqueous suspension slurry was uniformly coated onto the titanium substrate surface to be coated using an air spraying method. The thickness of the wet film was controlled to be 0.3 mm per coat. After each coating, the substrate was placed in a 60°C oven for 45 min to dry. After cooling to room temperature, the next coating was carried out. The coating and drying operations were repeated a total of 4 times to obtain a coating precursor with a continuous and uniform structure and a total dry film thickness of approximately 60 μm.
[0073] A titanium substrate with the coating precursor was placed in a muffle furnace, and the temperature was slowly increased to 450°C at a rate of 2°C / min while maintaining an air atmosphere throughout the process. The holding time was set to 2 hours. During the heating process, the aluminum polyphosphate binder phase underwent excessive decomposition and crystal transformation at high temperatures, resulting in a significant increase in the volume shrinkage of the coating. The internal thermal stress could not be effectively released, leading to a large number of obvious cracks on the coating surface, and in some areas, the coating peeled off from the titanium substrate interface.
[0074] After the heat treatment was completed, the ceramic coating was naturally cooled to room temperature in the furnace. After removal, a titanium suboxide ceramic coating prepared by high-temperature sintering was obtained. The integrity of the coating structure was significantly damaged, with prominent cracks and interface peeling defects. The enhanced life test verified that the coating failure time was only 32 hours. The oxygen evolution potential at a current density of 50 mA / cm² was as high as 2.10 V vs. SCE, and the conductivity and corrosion resistance were far lower than those of the example sample prepared by the low-temperature sintering process.
[0075] Comparative Example 4 Comparative Example 4 uses TA2 pure titanium sheet of the same specifications as in Example 1 as the substrate to be treated. The substrate pretreatment process and parameters are consistent with those in Example 1, and finally a rough and clean activated surface to be coated is obtained.
[0076] A sodium silicate solution with a modulus of 3.3 and a solid content of approximately 30% was used as a binder. This solution was mixed with deionized water and continuously stirred to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and sodium silicate. Anionic sodium polyacrylate dispersant was added to the binder base solution and stirred continuously until completely dissolved. The amount of dispersant used was 1% of the mass of the titanium suboxide powder. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base solution containing the dissolved dispersant. The addition process was accompanied by low-speed stirring to form a premixed slurry. The mass ratio of sodium silicate to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, followed by ultrasonic dispersion for 20 minutes to obtain an aqueous suspension slurry.
[0077] Aqueous suspension slurry was uniformly coated onto the titanium substrate surface using air spraying. The thickness of the wet film was controlled to be 0.3 mm per coat. After each coat, the substrate was dried in a 60°C oven for 45 min. After cooling to room temperature, the next coat was applied. The coating and drying process was repeated four times to obtain a coating precursor with a total dry film thickness of approximately 60 μm.
[0078] The titanium substrate with the coating precursor was placed in a muffle furnace and kept in an air atmosphere throughout. The temperature was slowly increased to 200°C at a rate of 2°C / min and held for 2 hours. After the holding period, the substrate was allowed to cool naturally to room temperature in the furnace. The resulting sodium silicate-bonded titanium suboxide coating was then obtained.
[0079] like Figure 7 As shown, at low magnification, the coating surface exhibits numerous penetrating cracks. These cracks extend along the boundaries of particle agglomerates, and in some areas, the coating shows flaking and localized peeling. The overall structural continuity is poor, failing to form a complete protective barrier. Figure 8 As shown, under high magnification, the interface between the sodium silicate binder phase and the titanium suboxide particles is loose, the particle edges are exposed and loose, the binder phase fails to fully encapsulate the particles and fill the gaps, and there are obvious gaps at the interface between the particles and the binder phase, which cannot form a dense and continuous bonded network.
[0080] Enhanced life testing verified that the coating experienced a sudden increase in cell voltage after 48 hours of electrolysis, indicating coating failure. Linear scanning voltammetry showed that its oxygen evolution potential in the same electrolyte was 1.41V vs. SCE, indicating that its conductivity and corrosion resistance were far lower than those of the example sample prepared with aluminum dihydrogen phosphate as a binder. This verified the key role of aluminum dihydrogen phosphate as a binder in ensuring the structural integrity and service performance of the coating.
[0081] Comparative Example 5 Comparative Example 5 uses TA2 pure titanium sheet of the same specifications as in Example 1 as the substrate to be treated. The substrate pretreatment process and parameters are consistent with those in Example 1, and finally a rough and clean activated surface to be coated is obtained.
[0082] A 40% (w / w) aqueous solution of aluminum dihydrogen phosphate was mixed with deionized water and stirred continuously to form a binder base solution. The total amount of water used was three times the total mass of the titanium suboxide powder and aluminum dihydrogen phosphate. No sodium polyacrylate dispersant was added during the preparation process. Pure Ti3O5 titanium suboxide powder with a median particle size of 200 nm was slowly added to the binder base solution, accompanied by low-speed stirring to form a premixed slurry. The mass ratio of aluminum dihydrogen phosphate to titanium suboxide powder was controlled at 1:3. The premixed slurry was first mechanically stirred for 30 minutes, followed by ultrasonic dispersion for 20 minutes to obtain an aqueous suspension slurry.
[0083] Take the slurry that is stirred evenly immediately and apply it to the activated surface of the titanium substrate in one go using air spraying. The wet film thickness is about 1.2 mm. During the coating process, due to the uneven flow of the slurry, obvious sagging and particle accumulation occurred in some areas. After coating, the titanium substrate was placed in a 60℃ oven to dry for 45 min. After drying, obvious shrinkage cracks appeared on the surface of the film, and blistering and delamination defects caused by uneven moisture migration were visible inside.
[0084] A titanium substrate with the coating precursor was placed in a muffle furnace under an air atmosphere throughout the process, and slowly heated to 450°C at a rate of 2°C / min, with a holding time of 2 hours. During the heating process, aluminum dihydrogen phosphate underwent excessive thermal decomposition above 300°C, causing the aluminum polyphosphate network structure to collapse and the binder phase to lose its effective consolidation ability for functional particles. Simultaneously, the coating volume shrinkage rate increased significantly, and internal thermal stress accumulated rapidly, leading to numerous through-cracks in the coating, severe warping and peeling at the edges, and partial exposure of the titanium substrate. After the holding time, the substrate was allowed to cool naturally to room temperature with the furnace, ultimately resulting in severe damage to the coating structure and complete detachment in some areas.
[0085] like Figure 9 As shown, at low magnification, the coating surface has multiple wide through cracks that divide the coating into discrete blocky areas. The coating as a whole is in a cracked and damaged state, with numerous pores and uneven defects on the surface. Obvious coating warping and peeling marks are visible at the edges, and the titanium substrate is partially exposed. The coating has lost its complete protective and conductive functions.
[0086] Enhanced life testing revealed that the coating already exhibited severe cracks and peeling defects before testing. After anodic polarization, the acidic electrolyte rapidly penetrated along the cracks into the titanium substrate, leading to rapid passivation of the substrate and large-area coating peeling. The tank voltage irreversibly increased within 18 hours, indicating coating failure. Linear scanning voltammetry determined the initial oxygen evolution potential to be 1.82 V vs. SCE. This value corresponds to an abnormal electrode state with severe coating cracking and localized substrate exposure, offering little practical reference value and lacking engineering application value. This confirms the necessity of the synergistic effect of dispersant addition, multiple thin coating layers, and low-temperature sintering in ensuring the coating's structure and performance.
[0087] like Figure 10 As shown, a systematic comparative test was conducted on the enhanced lifetime and oxygen evolution potential of each embodiment and comparative sample. The results show that the titanium suboxide ceramic coating on the titanium substrate surface prepared by the technical solution of the present invention has significantly better overall service performance than each comparative sample.
[0088] The enhanced lifetime of Examples 1 to 5 all remained above 120 hours, and the oxygen evolution potential at a current density of 50 mA / cm² remained stable in the range of 1.52~1.58V vs. SCE, exhibiting both stable conductivity and long-term corrosion resistance. Among them, Example 5, with a 2:1 mass ratio of Ti4O7 and Ti3O5, showed the best overall performance, with an enhanced lifetime of 148 hours. This indicates that the two types of sub-titanium oxide particles are mutually graded and filled, which can further improve the density of the coating and the continuity of the conductive path, thereby optimizing and improving service stability.
[0089] Comparative Example 1, without the addition of sodium polyacrylate dispersant, exhibited poor slurry suspension stability, leading to uneven coating composition and a loose structure. Its strengthening life was reduced to 55 hours, only about 46% of that in Example 1, directly verifying the crucial role of the dispersant in slurry dispersion uniformity and coating quality. Comparative Example 2 employed a single-coat thick-coating process. During drying and sintering, shrinkage stress could not be released layer by layer, resulting in numerous through-cracks in the coating and a strengthening life of only 25 hours. This indicates that multiple thin-coatings are a necessary process condition to ensure the integrity of the coating structure. Comparative Example 3 used high-temperature sintering at 450℃. Excessive decomposition and failure of the aluminum polyphosphate binder phase led to severe coating cracking and peeling, resulting in a strengthening life of only 32 hours. This confirms that the low-temperature sintering window defined in this invention is a core prerequisite for maintaining the structural stability of the binder phase and the bonding strength of the coating.
[0090] Comparative Example 4 used sodium silicate solution instead of aluminum dihydrogen phosphate as a binder. The bonding between the binder phase and the functional particles was loose and exhibited crack patterns, reducing the enhanced lifespan to 48 hours. This demonstrates that the aluminum dihydrogen phosphate inorganic binder system has irreplaceable advantages in interfacial bonding and acid corrosion resistance. Comparative Example 5 combined the three adverse factors of no dispersant, one-time thick coating, and high-temperature sintering, resulting in severe coating structure damage, large-area exposure of the substrate, and an enhanced lifespan of only 18 hours. This further illustrates the synergistic effect between the slurry formulation and process parameters of this invention, and that the high-performance conductive and corrosion-resistant coating can only be obtained through the combined effect of various key technical features.
[0091] Overall test results show that the synergistic effect of sodium polyacrylate dispersion regulation, multiple thin-coating molding, and low-temperature bonding and curing of aluminum dihydrogen phosphate is the core guarantee for preparing titanium-based titanium suboxide ceramic coatings with complete structure, strong bonding, and long service life. None of the three can be missing.
[0092] In summary, this invention addresses the technical problems of existing titanium-based titanium suboxide coating preparation, which relies on high-temperature reducing atmospheres, involves complex processes, and suffers from easy cracking and peeling, as well as insufficient adhesion to the substrate. It employs an inorganic binder system of aluminum dihydrogen phosphate combined with a layer-by-layer thin-coating low-temperature curing process to prepare a conductive and corrosion-resistant titanium suboxide ceramic coating on the surface of a titanium substrate. Sodium polyacrylate dispersant is used to regulate the uniformity of slurry suspension, and multiple thin coatings and interlayer mutual dissolution bonding gradually release drying shrinkage stress. Finally, the coating can be completely cured in an air atmosphere at 180-220℃, eliminating the need for reducing protective gases such as hydrogen, significantly simplifying the preparation process and reducing equipment requirements and energy consumption. The resulting coating has a dense and continuous structure, a strong bond to the titanium substrate, and is free of penetrating cracks and peeling defects. Its service life is significantly improved under strong acidic electrolysis conditions, and it possesses both stable conductivity and corrosion resistance. It can be widely used in the preparation of titanium-based electrodes and protective components in electrochemical water treatment, hydrometallurgy, and other fields.
[0093] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.
[0094] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate, characterized in that, Includes the following steps: The titanium substrate is subjected to degreasing, sandblasting, and acid etching in sequence to obtain a rough and clean surface to be coated. Titanium suboxide powder, aluminum dihydrogen phosphate inorganic binder, sodium polyacrylate dispersant, and deionized water are mixed and thoroughly stirred to obtain a uniform and stable aqueous suspension slurry. The titanium suboxide is Ti4O7 and / or Ti3O5, and the particle size of the titanium suboxide powder is 50nm~500nm. The mass ratio of binder to titanium suboxide powder is 1:2~1:5, the amount of dispersant is 0.5%~2% of the mass of titanium suboxide powder, and the amount of water is 2~5 times the total mass of titanium suboxide powder and aluminum dihydrogen phosphate. The aqueous suspension slurry is uniformly coated onto the surface of a titanium substrate to form a single-layer wet film, which is then dried in an environment of 50~70℃ to remove free water. After the coating cools to room temperature, the coating-drying operation is repeated 3~5 times to obtain a coating precursor with a total dry film thickness of 20~100μm. A titanium substrate with a coating precursor is placed in an air atmosphere and heated to 180-220°C at a rate of 1-3°C / min and held for 0.5-3 hours. Aluminum dihydrogen phosphate forms a continuous phosphate binder phase through a dehydration condensation reaction, and finally a sub-titanium oxide functional ceramic coating is obtained.
2. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 1, characterized in that, The step of mixing titanium suboxide powder, aluminum dihydrogen phosphate inorganic binder, sodium polyacrylate dispersant, and deionized water, and thoroughly stirring and dispersing them to obtain a uniform and stable aqueous suspension slurry includes: Take an aqueous solution of aluminum dihydrogen phosphate with a mass concentration of 30%~50%, mix it with deionized water and stir evenly to obtain the binder base liquid; Add sodium polyacrylate dispersant to the adhesive base liquid and stir until completely dissolved; the sodium polyacrylate is an anionic polyelectrolyte dispersant. Add titanium suboxide powder to the binder base liquid containing the dispersant, and stir initially to form a premixed slurry; the titanium suboxide powder is Ti4O7 and / or Ti3O5; The premixed slurry was subjected to mechanical stirring and ultrasonic dispersion treatment in sequence to obtain a stable aqueous suspension slurry with a solid content of 25%~35%.
3. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 1, characterized in that, The titanium suboxide powder is composed of Ti4O7 and Ti3O5 in a mass ratio of 1:2 to 2:
1.
4. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 1, characterized in that, The step of forming a continuous phosphate binder phase by the aluminum dihydrogen phosphate through a dehydration condensation reaction includes: During the heat preservation process, the aluminum dihydrogen phosphate gradually loses its water of crystallization; The titanium suboxide particles are encapsulated and bonded to the surface of the titanium matrix by a continuous network structure formed by intermolecular dehydration condensation, and then solidified into a phosphate glass phase bonding layer after cooling.
5. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 4, characterized in that, The phosphate glass phase bonding layer is an amorphous aluminum polyphosphate continuous network; The continuous network of aluminum polyphosphate simultaneously forms Ti-OP chemical bonds with the oxide layer on the surface of the titanium matrix, and forms physical encapsulation and chemical bonds with the sub-titanium oxide particles.
6. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 1, characterized in that, The steps of uniformly coating the aqueous suspension slurry onto the surface of the titanium substrate to form a single-layer wet film, drying it in an environment of 50~70℃ to remove free moisture, and repeating the coating-drying operation 3~5 times after the coating cools to room temperature include: The aqueous suspension slurry is coated onto the surface of the titanium substrate by brushing, dip-coating, or spraying, with the thickness of the wet film controlled at 0.2~0.5 mm per coat. After each coating, the titanium substrate is placed in a 60°C oven to dry for 30-60 minutes to evaporate the free moisture in the coating and form a dry film. After each drying process, the titanium substrate is removed from the oven and allowed to cool naturally to room temperature before the next coating is applied. Repeat the above operation 3 to 5 times to finally obtain a coating precursor with a total dry film thickness of 20 to 100 μm.
7. The method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate according to claim 6, characterized in that, After each drying process, the titanium substrate is removed from the oven and allowed to cool naturally to room temperature before the next coating is applied. This process includes: A single drying process removes free water from the slurry, while aluminum dihydrogen phosphate in the dry film retains some water of crystallization and maintains its binding activity. No grinding or roughening treatment is required between layers. During the next coating, the upper slurry and the lower dry film surface will mutually dissolve and bond, forming an integral coating without obvious interlayer interfaces.
8. A conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate, characterized in that, The coating is a composite ceramic layer attached to the surface of a titanium substrate, comprising a titanium suboxide functional phase and a phosphate binder phase; The coating is prepared by the method for preparing a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate as described in any one of claims 1 to 7.
9. The conductive and corrosion-resistant sub-titanium oxide ceramic coating on the titanium substrate surface according to claim 8, characterized in that, include: The sub-titanium oxide functional phase is Ti4O7 and / or Ti3O5; The phosphate binder phase is an amorphous, continuous network structure that encapsulates the titanium suboxide particles and fills the interparticle gaps. A Ti-OP chemically bonded transition layer exists at the interface between the coating and the titanium substrate.
10. The application of a conductive and corrosion-resistant sub-titanium oxide ceramic coating on a titanium substrate surface, characterized in that, A titanium substrate with a sub-titanium oxide ceramic coating is placed in an acidic electrolyte system with a pH of 1 to 6 and used as an anode under a current density of 100 to 2000 A / m².